RANCANG BANGUN MARKETPLACE PRODUK UMKM DI KABUPATEN NATUNA MENGGUNAKAN MODEL PROTOTYPING - Muhammad Andi Wibowo; Purwanto, Hari Lugis; Susanto, Gaguk (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2024)
Natuna Regency, a potential region in tourism, fisheries, plantations, and SMEs, faces challenges in digital SME marketing. Constraints involve product limitations, brand image difficulties, and cross-border regulatory complexity. This study designs a web-based SME product sales information system in Natuna using a prototyping model, emphasizing SME empowerment. Through prototyping, system development ensures interactive involvement between developers and users, making the system more responsive to user needs. User Acceptance Test results indicate 88,58% of respondents agree that this system can positively contribute to the local economy and facilitate SME growth in Natuna Regency.